INSTAGRAM SEBAGAI MEDIA PROMOSI DALAM MENINGKATKAN PENGEMBANGAN BISNIS SEBAGAI MUA OLEH NANATH NADIA - Mia Tania (ADISAM PUBLISHER, 2025)
The use of digital-based media currently influences any aspects, including lifestyle, business, communication and the use of information media. Media social one popular of digital media used by public, one of the social media that is widely used is Instagram. In the business program, Instagram is currently one of media sosial used by Nanath Nadia as Make Up Artist (MUA). The aim of this research is to determine the role of Instagram as a promotional to increase the number of service users at Nanath Nadia MUA. The sampling technique used was purposive sampling. This research method uses descriptive research with a qualitative approach. Data collection was carried out through interviews and documentation. The informants in this research are business owners and influencers. The data analysis techniques use data reduction, data presentation and drawing conclusions. The results of this research show that Nanath Nadia MUA has used Instagram as a promotional media. The results of this research show that there are four factors that determine Nanath Nadia MUA choosing Instagram, such as media for relations, publicity, promotion, market research. Nanath Nadia MUA's promotional activities by Instagram such as use any fiture, instastories, ads, reels, live feeds, quizzes and polls. The implication of Instagram for Nanath Nadia MUA is that it can provide an increase in both the quality and quantity of users of its makeup services